Anxiety in College Students With ADHD: Relationship to Cognitive Functioning. (March 2015) - Prevatt, Frances; Dehili, Vincent; Taylor, Nicki; Marshall, Diana
Objective: This study sought to explore how anxiety impacts college students with ADHD, especially with regard to cognitive functioning.Method: 473 college students with ADHD and a control group of 200 college students without ADHD completed self-report measures of anxiety, ADHD symptomatology and tests of cognitive functioning.Results: Students with ADHD reported significantly more anxiety than students without ADHD. Within the ADHD group, the relationship between anxiety and inattention was similar to the relationship between anxiety and hyperactivity/impulsivity. Students with ADHD reported more anxiety with regard to academics compared to life-in-general. There were no gender differences for anxiety; however, freshman indicated more anxiety than upper-classmen. Anxiety and inattention were found to interact such that students with low levels of inattention but high levels of anxiety performed better on tasks of cognitive ability.Conclusion: Anxiety in college students with ADHD can take many forms, and interventions require a multi-focused approach. There may be some positive aspects to anxiety.